Men, Women & Children - Kultgen, Chad, 1976- (New York : Harper Perennial, 2011)
Explores the sexual pressures at work upon two generations navigating the online world, following the lives and addictions of such characters as Dawn, a single mom who charges men money to view suggestive online pictures of her daughter.
Keywords: Single people -- Sexual behavior; Fiction; Junior high school teachers -- Sexual behavior; Fiction; Internet -- Social aspects; Fiction; Mass media and sex -- Fiction; Black humor